Correlates of social exclusion and negative labeling and devaluation of people living with HIV/AIDS in rural settings: evidence from a General Household Survey in Zambézia Province, Mozambique. - Abraham Mukolo (Public Library of Science (PLoS), 2013)
Background Increased HIV/AIDS knowledge and access to antiretroviral treatment (ART) have been hypothesized to decrease HIV stigma. However, stigma persists as a barrier to HIV services uptake. We studied the relationship between stigma, knowledge and attitudes towards HIV and its treatment, and confidence in the legal system (legal rights certitude). Methods We analyzed data from a household survey of 3749 randomly sampled female heads of households in 259 enumeration areas across 14 districts of Zambézia Province, Mozambique. The questionnaire included questions about beliefs, attitudes and behavior towards PLWHA, HIV transmission knowledge, treatment-related beliefs, and legal rights certitude. Factor analysis distinguished two stigma constructs: Negative labeling and devaluation (NLD) and social exclusion (SoE). Multivariable linear regression was used to determine the association between stigma, knowledge of HIV/AIDS, treatment-related beliefs, and legal rights certitude, while controlling for variance in socio-demographics. Results A 4-point increase in knowledge about HIV transmission was associated with more than a 3 unit decrease in NLD and SoE stigma scores (p<0.001). Given HIV transmission knowledge, a 25-point increase in legal rights certitude was associated with a 4.62 unit drop in NLD stigma (p<0.001); we did not detect an association between legal rights certitude and SoE stigma. Knowing at least one HIV positive person was associated with lower SoE (-3.17, 95% CI: -5.78, -0.56); no association with NLD (p = 0.1) was detected. ART efficacy belief was associated with higher NLD and lower SoE (2.90 increase and 6.94 decrease, respectively; p ≤ 0.001). Conclusion Increasing knowledge about HIV transmission and access to ART are likely to reduce stigma, but neither of the two is a panacea. Raising community awareness of the legal rights of PLWHA might improve the efficacy of stigma reduction efforts. Strategies that focus on specific domains of stigma might be more effective than generic stigma reduction strategies.